2015
DOI: 10.1007/s12124-015-9312-8
|View full text |Cite
|
Sign up to set email alerts
|

Primates’ Socio-Cognitive Abilities: What Kind of Comparisons Makes Sense?

Abstract: Referential gestures are of pivotal importance to the human species. We effortlessly make use of each others' referential gestures to attend to the same things, and our ability to use these gestures show themselves from very early in life. Almost 20 years ago, James Anderson and colleagues presented an experimental paradigm with which to examine the use of referential gestures in non-human primates: the object-choice task. Since then, numerous object-choice studies have been made, not only with primates but al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 80 publications
0
2
0
Order By: Relevance
“…These findings demonstrate that dogs and nonhuman primates are treated systematically differently across the OCT literature. They differ in the quality of their early interactions with humans, they are tested in different physical circumstances, they are tested with different cues to locations presented in different spatial configurations, etc., and these systematic differences have been noted by every extant review of OCT studies (Byrnit, 2015;Lyn, 2010;Mulcahy & Hedge, 2012). Moreover, dogs and nonhuman primates differ in many additional respects, in body plan, in longevity, in the relative durations of successive life history stages, and so on.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings demonstrate that dogs and nonhuman primates are treated systematically differently across the OCT literature. They differ in the quality of their early interactions with humans, they are tested in different physical circumstances, they are tested with different cues to locations presented in different spatial configurations, etc., and these systematic differences have been noted by every extant review of OCT studies (Byrnit, 2015;Lyn, 2010;Mulcahy & Hedge, 2012). Moreover, dogs and nonhuman primates differ in many additional respects, in body plan, in longevity, in the relative durations of successive life history stages, and so on.…”
Section: Discussionmentioning
confidence: 99%
“…Mulcahy and Hedge (2012) reviewed 63 OCT papers and concluded that configurational differences in the testing of apes and dogs disadvantage the former due to decreased salience of, and attention, to the cue being given. Finally, in a review of gazefollowing OCT studies with nonhuman primates Byrnit (2015) argues that there exists such disparity between different species in their performance on the OCT that taking one species' results as representative of their whole phylogenetic group leads to erroneous conclusions.…”
mentioning
confidence: 99%